Penerapan Media Pembelajaran Dengan Aplikasi Ideal Dictionary Di SDN Megaluh - Sa'adah, Lailatus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
In the era of increasingly developing technology, almost all subjects use internet media. The android-based English Learning Application is a learning medium that is used interactively in understanding vocabulary that is easy for students to understand. The intended subject of this activity is a grade IV student of SDN Megaluh. The problem experienced by grade IV students of SDN Megaluh is that they do not get English lessons from the first to third grades due to the independent curriculum which results in them not getting English language learning. The purpose of creating this learning media is to make it easier for students to get to know some basic vocabulary in English. The methods used in this case are twofold, namely the lecture method and the question and answer method. Both of these methods are used to find out the needs of students. From the analysis with these two methods, an ideal dictionary application was created where this application will support learning. It is hoped that this application can later be developed again by SDN Megaluh to support English learning, especially for students who are still new to English lessons. Because this kind of application if developed in the future becomes a learning medium that is quite interesting for students.